Kajian etnobotani masyarakat adat suku moronene di Taman Nasional Rawa Aopa Watumohai - Heru Setiawan; Maryatul Qiptiyah (Jurnal Penelitian Kehutanan Wallacea, 2014)
The Moronene ethnic living in the forests of Rawa Aopa Watumohai National Park has strong interaction with nature and environment around the park. The interaction of indigenous people with their environment produced the wisdom to manage the natural resources for sustainable benefit. This study was aimed to comprehend various forms of plants utilizations by this local community. The method used is field survey, included interviews, plant identification and data analysis. The data was collected by semi-structured interviews with respondents. Plant specimen collection was conducted together with key informants. The data was analyzed with descriptive qualitative method. The utilization of plants by indigenous peoples of Moronene tribe is divided into three major groups, including for food, medicine and traditional ceremony. As much as 124 species, including 68 species for food, 65 species for medicine and 10 species for traditional ceremony were identified.